Maintenance of response after open-label treatment with atomoxetine hydrochloride in international European and non-European adult outpatients with attention-deficit/hyperactivity disorder: a placebo-controlled, randomised withdrawal study - Upadhyaya, Himanshu; Ramos-Quiroga, J. Antoni; Adler, Lenard A.; Williams, David; Tanaka, Yoko; Lane, Jeannine R.; Escobar, Rodrigo; Trzepacz, Paula; Camporeale, Angelo; Allen, Albert J. (The European journal of psychiatry, 2013)
Background and Objectives: We evaluated maintenance of response to atomoxetine during a 25-week, double-blind, placebo-controlled, randomised withdrawal period in adults with attention-deficit/hyperactivity disorder (ADHD) who previously responded to atomoxetine during a 12 week open-label treatment period and maintained that response during a 12-week double-blind maintenance period. Methods: Patients (N = 2017), 18 to 50 years of age, diagnosed with ADHD from 152 outpatient sites in 18 countries received 12 weeks of open-label atomoxetine (40-100 mg/day) followed by 12 weeks of double-blind maintenance (80 or 100 mg/day). Responders were randomized to atomoxetine (N = 266) or placebo (N = 258) for 25-weeks of double-blind treatment. The percentage of patients with a reduction >30% in their baseline Conners' ADHD Rating Scale Investigator-Rated: Screening Version (CAARS-Inv:SV) total score and a score of <3 on the Clinical Global Impression ADHD-Severity (CGI-ADHD-S) after 25 weeks was compared between treatment groups with a Fisher's exact test. Mean changes from baseline in the CAARS-Inv:SV and Adult Attention-Deficit/Hyperactivity Disorder Quality of Life (AAQoL) were analysed. Results: Most patients enrolled (60%) were from Europe. More atomoxetine than placebo-treated patients maintained a satisfactory response postrandomisation (64.3% vs. 50.0%; p < .001). Time-to-relapse was significantly longer for atomoxetine than placebo (p = .004). Atomoxetine maintained greater improvements in ADHD symptoms compared with placebo (LS mean worsening in the CAARS-Inv:SV total score was 0.9 vs. 4.8 [p < .001] and in the CGI-ADHD-S rating was 0.0 vs. 0.5 [p < .001]). These results were supported by self- or observer-rated measures. Lastly, atomoxetine maintained greater improvements in quality of life compared with placebo (AAQoL total score was 0.4 vs. -4.0; p = .002). Adapted from the source document.